1994
DOI: 10.1084/jem.180.6.2407
|View full text |Cite
|
Sign up to set email alerts
|

CD30 expression by CD8+ T cells producing type 2 helper cytokines. Evidence for large numbers of CD8+CD30+ T cell clones in human immunodeficiency virus infection.

Abstract: SummaryA large panel of CD8 + T cell clones generated from peripheral blood lymphocytes (PBL) of healthy donors or human immunodeficiency virus (HIV)-infected individuals were assessed for both cytokine secretion profile and CD30 expression and release. The great majority of CD8 + T cell dones generated from healthy individuals showed the ability to produce interferon 3' (IFN-3'), but not interleukin 4 (IL-4), and none of them either expressed membrane CD30 or released substantial amounts of soluble CD30 (sCD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(79 citation statements)
references
References 15 publications
5
72
0
2
Order By: Relevance
“…Also the study of cytokine production profiles can be used for this purpose: a switch from Th1 to Th2 cytokine-producing cells in the course of the disease has been suggested to be associated with deteriorating immunological functions [9,19]. Previous studies have also shown that CD28 and IL-2 production are reduced in HIV infection, and that in HIV , but p24-negative subjects, IL-2 is a key factor of the immunological response, because of its ability to reduce the mortality of CD8 CD28 non-activated cells [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also the study of cytokine production profiles can be used for this purpose: a switch from Th1 to Th2 cytokine-producing cells in the course of the disease has been suggested to be associated with deteriorating immunological functions [9,19]. Previous studies have also shown that CD28 and IL-2 production are reduced in HIV infection, and that in HIV , but p24-negative subjects, IL-2 is a key factor of the immunological response, because of its ability to reduce the mortality of CD8 CD28 non-activated cells [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a dichotomy of Th1 and Th2 predominance in HIV-infected individuals has been recently debated [9,10,19,24]. Some authors suggest that large numbers of CD8 clones from these patients produce type 2 helper cytokines [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly dynamic pathogenic mechanisms involved in the earliest phase of HIV infection are complex and not yet fully elucidated [1][2][3]. Among them, a relevant role is probably played by CD30-CD30 ligand (CD30L) interactions, as suggested by several recent findings [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Among them: (i) the up-regulation of CD30 expression and sCD30 release following in vitro HIV infection of CD4 + Th2-type clones [4,6], i.e. those functionally characterized T cells in which HIV replication preferentially occurs [13]; (ii) evidence that CD30 triggering promotes viral replication in infected cells [5][6][7]; (iii) the ability of CD30 cross-linking to activate NF-kB [7,14], which is known to induce the HIV long terminal repeat leading to virus synthesis in infected cells [15]. In addition, we previously demonstrated that serum levels of sCD30 soon after seroconversion represent a prognostic parameter in patients with HIV infection [11].…”
Section: Introductionmentioning
confidence: 99%